2021
DOI: 10.1111/wvn.12503
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Clinical Barriers and Evidence‐Based Implementation Strategies in Low‐to‐Middle Income Countries (LMICs)

Abstract: Background: Low-to-middle income countries (LMICs) experience a high burden of disease from both non-communicable and communicable diseases. Addressing these public health concerns requires effective implementation strategies and localization of translation of knowledge into practice.Aim: To identify and categorize barriers and strategies to evidence implementation in LMICs from published evidence implementation studies.Methods: A descriptive analysis of key characteristics of evidence implementation projects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 31 publications
4
8
0
Order By: Relevance
“…The results suggest that personal, interpersonal and institution barriers exist regarding adoption or implementation of recommended WHO guidelines on maternal and newborn health. This finding concurred with reviews which found that while the barriers identified are broadly similar in theme to those reported from high-income settings, their specific nature often differs as it is contextual [ 44 , 47 ]. For instance, at an individual level, lack of interest in the evidence supporting guidelines, poor motivation for using the guidelines, subjective feelings that following new recommendations may erode interpersonal relationships with clients or erode professionalism, and expectations of providing individualized care may threaten successful implementation [ 44 ].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The results suggest that personal, interpersonal and institution barriers exist regarding adoption or implementation of recommended WHO guidelines on maternal and newborn health. This finding concurred with reviews which found that while the barriers identified are broadly similar in theme to those reported from high-income settings, their specific nature often differs as it is contextual [ 44 , 47 ]. For instance, at an individual level, lack of interest in the evidence supporting guidelines, poor motivation for using the guidelines, subjective feelings that following new recommendations may erode interpersonal relationships with clients or erode professionalism, and expectations of providing individualized care may threaten successful implementation [ 44 ].…”
Section: Discussionsupporting
confidence: 84%
“…Failure to recognize and appreciate good work or good performance; poor communication and lack of team teamwork; organizational constraints (such as organization of care, duty coverage and staffing norms) and limited resources (both financial and non-financial) are also notable barriers. Counterproductive health worker norms (such as absenteeism); absence of perceived benefits or incentives linked to adoption of new practices; difficulties accepting change and failure to adopt new changes; lack of client motivation; and conflicting attitudes and beliefs (of both the clients and healthcare providers) do hinder guideline adoption and were noted in this study [ 41 , 44 46 ]. These barriers may largely be because guidelines are adopted from high income settings and there may be little or no involvement of the end user in the development of those that are developed in low income settings [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The investigators' next steps are to use this evidence as a guide for organizational infrastructure to support the culture and implementa- All frontline staff nurses should be accountable for embracing and advancing evidence in professional practice and patient care (Crawford & Scott, 2011;Speroni et al, 2020;Whitehorn et al, 2021). While past recommendations frequently focus on senior management and executive leaders creating and supporting EBP (Berthelsen & Hølge-Hazelton, 2021;McNett et al, 2021;Shuman et al, 2019), professional nurse engagement must also be emphasized, along with science-based strategies to enhance professionalism and continued growth of system-wide EBP culture.…”
Section: Implications and Recommendationsmentioning
confidence: 99%
“…It incited codesigning of culturally sensitive, relevant SBC approaches, including appropriate measures that reflected the lived experiences of the target population, while addressing data collection and usage constraints across all levels. 16 iDARE teams must always consist of the relevant local stakeholders, with particular attention to inclusivity and representation of all actors within the socioecological environment.…”
Section: Discussionmentioning
confidence: 99%